The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1098/rstb.2021.0179
|View full text |Cite
|
Sign up to set email alerts
|

Laughter and culture

Abstract: Like most human non-verbal vocalizations, laughter is produced by speakers of all languages, across all known societies. But despite this obvious fact (or perhaps because of it), there is little comparative research examining the structural and functional similarity of laughter across speakers from different cultures. Here, we describe existing research examining (i) the perception of laughter across disparate cultures, (ii) conversation analysis examining how laughter manifests itself during discourse across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…The majority of the items that loaded onto these three principal components in the English version of the questionnaire also loaded onto the same components in the Chinese version. These results are consistent with prior research demonstrating the cross-cultural recognition of laughter as a non-verbal vocalization(Bryant & Bainbridge, 2022;Sauter et al, 2010). Specifically, these findings suggest that laughter is universally perceived and produced as a positive expression across all societies, as evidenced by the similar loadings on Frequency and Liking of laughter of the laughter questionnaire.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The majority of the items that loaded onto these three principal components in the English version of the questionnaire also loaded onto the same components in the Chinese version. These results are consistent with prior research demonstrating the cross-cultural recognition of laughter as a non-verbal vocalization(Bryant & Bainbridge, 2022;Sauter et al, 2010). Specifically, these findings suggest that laughter is universally perceived and produced as a positive expression across all societies, as evidenced by the similar loadings on Frequency and Liking of laughter of the laughter questionnaire.…”
supporting
confidence: 90%
“…Previous studies have primarily focused on the cross-cultural perception and recognition of laughter (Bryant & Bainbridge, 2022;Sauter et al, 2010), whereas this study is the first to explore the self-reported experience of laughter across cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then four reviews frame laughter studies in the fields of anthropology (Dunbar [ 2 ]), ethology (Davila-Ross & Palagi [ 3 ]), psychology (Scott et al . [ 4 ]) and cross-cultural studies (Bryant & Bainbridge [ 5 ]). A second section is entirely dedicated to new empirical data, with studies tackling the issue of laughter in the fields of behavioural studies (Burke et al .…”
Section: Introductionmentioning
confidence: 99%
“…Then four reviews frame laughter studies in the fields of anthropology (Dunbar [ 2 ]), ethology (Davila-Ross & Palagi [ 3 ]), psychology (Scott et al . [ 4 ]) and cross-cultural studies (Bryant & Bainbridge [ 5 ]).…”
Section: Introductionmentioning
confidence: 99%